2013
DOI: 10.1080/17452007.2013.837254
|View full text |Cite
|
Sign up to set email alerts
|

Occupancy analytics: a new basis for low-energy–low-carbon hospital design and operation in the UK

Abstract: This paper introduces an innovative approach to low-energy-low-carbon design for a new hospital in the UK. This innovation is achieved through an analysis of hospital operational policies and the impact of them on this performance. The analysis leads to new information and data, and it will be explained how this has a significant impact on the engineering design for the hospital's environmental systems. The work is a significant point of departure from conventional design practice, which largely focuses on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…The absence of good quality data (i.e. data relating to energy and thermal requirements) on which to base engineering designs, is another contributing factor to the oversizing issue that leads to many estimates and assumptions being made, and hence the prolific application of cumulative margins, by various stakeholders, to safeguard against any uncertainties or risks (Bacon, 2014).…”
Section: Margins Leading To Overdesignmentioning
confidence: 99%
“…The absence of good quality data (i.e. data relating to energy and thermal requirements) on which to base engineering designs, is another contributing factor to the oversizing issue that leads to many estimates and assumptions being made, and hence the prolific application of cumulative margins, by various stakeholders, to safeguard against any uncertainties or risks (Bacon, 2014).…”
Section: Margins Leading To Overdesignmentioning
confidence: 99%
“…Another survey conducted among engineers in Hong Kong reveals that 67% of respondent intentionally oversized the calculation by 10-15% 14) . Bacon attributed this phenomenon due to the need of engineers to eliminate uncertainties which leads to calculation based on worst case scenarios especially to unspecified parameters such as occupancy level, infiltration and lighting intensity 15) . Proctor et al even reported of some industry player practice of ignoring sound engineering judgement to suit commercial purpose 16) .…”
Section: Introductionmentioning
confidence: 99%
“…Over-engineering of building service systems is often a hidden source of inefficiency that can significantly add to building operational costs, and reduce the sustainability of systems (Bacon, 2014). This paper provides an overview of the issue of overdesign in building services that results from the excessive and uncoordinated application of design margins.…”
Section: Introductionmentioning
confidence: 99%